The Waterfront project in Naples - Leonardi, Robert (TeMA - Journal of Land Use, Mobility and Environment, 2009)
In the last decade Naples the port of Naples has rediscovered its wide-ranging role not merely concerned with the sea but also with the adjacent city. A strong connection has now returned between Naples and its port: the elimination of the barriers around the port and the pedestrianisation of the tourist area will help to link the city with its port and, as a consequence, with the sea. The rationalisation and specialisation plans of the port area mean that the port will become an increasingly dynamic force working in harmony with the city and its hinterland. Now no longer an obstacle, the port of Naples has a wide range of activities (commercial, productive, tourism and cultural) which all use the sea as a point of exchange, transformation and growth. One of the principal project of the reconnection of the port of Naples and the surrounding city is the Waterfront Project. The Waterfront project take part of a bigger renewal process that the city of Naples and the Port authority of Naples are working on, that and which is going to focus on the following issues: - Taking the cruise traffic to develop new attractive/ aggregative poles for cruise tourists and inhabitants on the waterfront in deprived areas. - Conjugating the safety theme with the permeability of the port by the inhabitants and the tourists and toning down the physical obstacles. - Rationalizing the organization of the port and improving the passenger port area. - Encouraging a better utilization of the historical and monumental heritage of the city and of the abandoned former industrial areas of the port and of the city-port interface. - Improving the governance of the projects of urban / port transformation for a real coordination between the different stakeholders involved in a shared management of the projects and of the objectives. In this context, the Waterfront project aims at: - improving the connection between port and city which will create a high quality tourist support for cruise passengers; - strengthening and rationalization of the logistic-port infrastructures, taking in account the multifunctional vocation of the port. - creating a positive economic impact for commercial and handicraft industrial areas close to the port - the re-qualification of the building heritage close to the port area with a subsequent increase and enhancement of the hosting infrastructures. - strengthening sustainable mobility will decrease the high level of atmospheric and acoustic pollution. - approaching the cruise activity is an opportunity to redevelop the industrial derelict areas in urban park and recreational/cultural places and to upgrade the quality of life.